Pendampingan Kader Dan Ibu Menyusui Dalam Upaya Peningkatan Produksi ASI Dengan Menggunakan Kompres Hangat Di Desa Bontomacinna Kab. Bulukumba - Syarifah Masita; Nur Hidayah MS Hidayah (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2022)
Infancy and toddlerhood are a golden period for growth and development and one of the first and best and natural nutritional fulfillment for infants is breastfeeding. Low milk production is the most common cause of failure in breastfeeding. The participation of community cadres in breastfeeding efforts is still lacking, assuming that if the baby is already drinking milk, both breast milk and formula, the mother does not need to increase her milk. The purpose of this community service is to increase the knowledge and skills of cadres and breastfeeding mothers about breast milk and milk production with warm compresses in Menganti Village. This service method is carried out with the following stages of activity: 1) Providing material and demonstration of warm compresses, 2) Simulation of warm compress practice to increase breast milk production 3) Evaluation of practice results and breast milk check-lists. The partners in this service are cadres and breastfeeding mothers. The result of this service is that cadres and breastfeeding mothers understand the skills of warm compresses and increase breast milk production in breastfeeding mothers. The conclusion should be frequent training on efforts to increase milk production for cadres, residents and breastfeeding mothers.